Means and ends toward the broadband society: Net neutrality and over-the-top players - Toshiya Jitsuzumi (International Telecommunications Society (ITS), 2015)
Because broadband is widely believed to be a precondition for economic prosperity and social progress, many governments have been improving the broadband environments in their respective countries. Net neutrality, which in its most basic form requires "equal" treatment for all Internet traffic, should be considered only as a means of improving broadband rather than as a stand-alone policy goal. Net neutrality has been a major topic of interest for telecom regulators in developed nations for nearly a decade. However, treating net neutrality as the ultimate target may prevent a more important goal from being achieved. Policy targets and priorities should be tailored to the broadband development stage of each market. In this study, the author argues that a strict net neutrality principle is not optimal and should be relaxed to accommodate the local needs of individual markets and reflect their development stages. In addition, discussion, especially in developed nations, should focus not on quality-of-service-based net neutrality but on quality-of-experience for optimal resource allocation.
Keywords: 330; broadband; net neutrality; QoS; QoE